(untitled) (Research, Society and Development, 2020)
Objective: In this context, the objective of this work is to present a literature review study on the popular use of medicinal plants to treat gastrointestinal disorders, identifying the main plants used to treat diseases, plants used in the treatment of gastrointestinal disorders and the social importance for the population. Methodology: Descriptive study of literature review, qualitative in nature on the popular use of medicinal plants to treat gastrointestinal disorders. The data collection period took place from July to November 2020 in the databases: Public Medline (PubMed), Scientific Eletronic Library Online (SciELO) e Virtual Health Library (VHL), by crossing keywords: Gastroenteropathies, medicinal plants, ethnobotany, herbal medicine, intestinal disorders, with publications from 2015 to 2020. Results: In the initial research, 136 articles were identified: PubMed (5), VHL (4), SciELO (125). After applying the “clinical trial” and “last five years” filters, excluding articles for not meeting the eligibility criteria, 9 potentially relevant studies remained for the review of articles for a detailed analysis. Conclusion: Phytopreparations are of fundamental importance in the precaution and treatment of various digestive disorders. The phytotherapy used is very tolerated, without strong sequelae and concomitantly, patients are happy with the visible or assumed changes.